Betel Nut Peel Powder as Biosorbent for Mg(II), Ca(II), and Fe(III) in Agricultural Water - Susiana, Carissa Ayu; Mukhayani, Feri; Simatupang, Erwinton; Pambudi, Fajar Inggit; Sumerta, I Wayan; Mulyanegara, Guntur; Samudin, Mohammad Nur; Prayoga, Dedo Kevin; Nuryono, Nuryono (Indonesian Journal of Chemistry, 2025)
Water pollution from heavy metal contamination is a global issue; finding low-cost and sustainable solutions is challenging. Among various methods, biomass adsorption is a practical approach for treating heavy metal contamination in agricultural water. This study explored the use of betel nut peel as a biosorbent to remove Mg(II), Ca(II), and Fe(III) ions from agricultural water. The adsorbent contained active groups like −OH, C=O, and C=C, indicating cellulose, lignin, and hemicellulose compounds. Mature betel nut peels showed higher adsorption capacities than immature ones due to their larger surface area and more active sites. The optimal adsorption occurred at an initial adsorbate concentration of 100 mg L−1 for 1 h, with 5 mg of biosorbent. The biosorbent followed the Langmuir isotherm and a pseudo-second-order kinetic model (R2 = 0.99), indicating chemisorption. When applied to agricultural water from South Sumatra, the biosorbent removed up to 90% of Fe(III) ions. These findings suggest that betel nut peel powder has strong potential as a biosorbent for heavy metals, with promising applications in water treatment and environmental remediation. It also shows potential as a biofertilizer, particularly for soils rich in Fe(III).